Elementary School PJOK Teachers' Perceptions of the Independent Learning - Badaru, Benny; Arfanda, Poppy Elisano; Hudain, Muh. Adnan; Mardiana, Mardiana; Arimbi, Arimbi (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This quantitative descriptive study aims to understand how PJOK SD teachers view independent learning in the district. South Polombangkeng, Takalar district. The population in this study consisted of 32 elementary school PJOK teachers in Takalar Regency. We collected data using techniques like observation, questionnaires, interviews, and documentation. We used descriptive analysis as a data analysis technique. In more detail, the results show that in the "excellent" category, it is 3.12% (1 teacher), the "good" category is 56.25% (18 teachers), the "fairly good" group is 34.38% (11 teachers), the "not good" category is 6.25% (2 teachers), and the "naughty" category is 0% (0 teachers). Referring to the average value of 124.34, which is included in the score interval 123.35 < X < 148.5, which indicates the good category, based on the results of the analysis, the research data on PJOK Elementary School teachers' perceptions of independent learning as a whole is good.